THE EFFECT OF CUSTOMER REVIEWS, PRODUCT PRICE, AND SERVICE QUALITY ON PURCHASE DECISIONS WITH MODERATED BRAND IMAGE IN E-COMMERCE APPLICATIONS - Wikantari, Maria Assumpta (Master of Management, Faculty of Economics and Business, Diponegoro University, 2023)
This study aims to analyze the effect of customer reviews, product prices and service quality on purchasing decisions moderated by brand image. The population in this study is 100 residents of the city of Jakarta, whose criteria have been determined. The sample selection was carried out using a purposive sampling method, by taking 100 Jakarta residents with an age range of 20-40 years as the sample in this study.The analytical techniques used in this study are: 1) Validity Test, 2) Reliability Statistics, 3) Classical Assumption Test consisting of Normality Test, Multicollinearity Test, Heterocystista Test, Autocorrelation Test, 4) Multiple Linear Regression, 5) Hypothesis Test consisting of from Coefficient Test and Partial Influence Test (t) and MRA.The results of this study indicate that customer reviews have no effect on purchasing decisions, this is evidenced by the t value of 0.747. Product prices have a significant effect with a t-value of 0.460. Service quality has a partial effect on purchasing decisions with a t value of 3.378. Customer reviews, product prices and service quality simultaneously influence purchasing decisions with an f value of 4.451. Brand image cannot mediate the relationship between customer reviews, product prices, service quality on purchasing decisions, and none of them are significant